Produtividade e qualidade de cultivares de melancia em função de doses de fósforo - Goncalves, Francisco das Chagas (2013)
The yield of Brazilian agricultural production in 2011 exceeded 68 billion reais and watermelon contributed with 0.5 % of this value (PAM 2011), but its potential is much higher than this, given that in many parts of Brazil people still cultivate open pollinated material in non irrigated land and, most times, the real nutritional needs of cultivars are unkonwn, as well as the portion of soil contribution to this nutrition, factors that contribute to low yield (20 t ha-1). Phosphorus, despite being one of the macronutrients less required by crops, is always used in large quantities, due to both its deficiency in Brazilian soils as its high degree of interaction with the soil. This work was accomplished in the period August to October 2012, aiming to evaluate the performance of two cultivars of watermelon in function of phosphorus doses in the conditions of Mossoró-RN. The experimental design was a randomized complete block in factorial 2 x 6 with four replications. Treatments consisted of six doses of phosphorus (0, 45, 90, 135, 180 and 225 kg ha-1 P2O5) and two cultivars of watermelon (Olympia and Top Gun). The cultivars differed with respect to the total and average commercial fruit weight, total soluble solids and shell thickness, and the Olympia topped the Top Gun for total and marketable fruit weight and average shell thickness, whereas the opposite occurred for total soluble solids. The phosphorus doses that resulted in the highest total number (1.97) and commercial (1.70) of fruits per plant were 77.22 and 54.75 kg ha-1 of P2O5, respectively. The maximum total yield (80.14 t ha-1) and maximum commercial (74.39 t ha-1) were obtained, respectively, with the doses of 54.3 and 49.4 kg ha-1 of P2O5. Phosphorus fertilization did not affect fruit quality. The cultivars showed differences in the foliar concentrations of all analyzed nutrients and phosphorus influenced the foliar concentrations of nitrogen, potassium, zinc and manganese